AUTHORITY TO ISSUES AN ORDER TO TERMINATE INVESTIGATION (SP3) IN CORRUPTION CASES - Nusantara Tarigan Silangit; Herlina Hanum Harahap; Muhammad Ansori Lubis (LPPM YPITI, 2026)
Corruption is an extraordinary crime because it is systemic, endemic, and has a very broad impact that not only harms state finances but also violates the social and economic rights of the wider community so that its action requires special efforts. Termination of investigation of corruption is carried out through the issuance of an Investigation Termination Order (SP3) by investigators (Police, Prosecutors, or the Corruption Eradication Commission). Based on legal validity if it meets the reasons for insufficient evidence: The investigator concludes that the existing evidence is insufficient to continue the case to the prosecution stage, the alleged incident does not fulfill the elements of a corruption crime, the case is stopped for reasons of the loss of the right to sue due to the suspect's death, expiration, or ne bis in idem (the same case has been decided by the court and has permanent legal force).